Mass Events as Key Drivers of Tourist Appeal in Samarkand City - Ibragimov Sardorbek Khusanovich (Academia Open, 2025)
General Background: The tourism sector is a strategic priority in Uzbekistan, with cultural heritage and gastronomy serving as key pillars. Specific Background: Samarkand, as a historical city, is central to national tourism development plans, with increased emphasis on leveraging mass events to boost destination appeal. Knowledge Gap: Despite international recognition of event tourism’s role, empirical evidence from Central Asia, particularly linking event frequency with tourist influx, remains limited. Aims: This study investigates the impact of mass cultural and gastronomic events on the attractiveness of Samarkand as a tourist destination, using correlation and regression analysis. Results: A strong positive correlation (r ≈ 0.98) was found between the number of mass events and tourist arrivals from 2017–2023. Regression analysis showed that each additional event increases tourist numbers by approximately 172,500. Novelty: The research provides one of the first quantitative models in Uzbekistan linking event tourism with visitor data, distinguishing between cultural and gastronomic tourism impacts. Implications: The findings support policy recommendations to institutionalize annual event calendars, integrate gastronomic branding, and align local stakeholder involvement with sustainable tourism strategies to enhance destination competitiveness.Highlight : Mass events in Samarkand show a strong positive correlation (r ≈ 0.98) with increased tourist arrivals. Combining cultural and gastronomic tourism creates a powerful, diversified attraction for visitors. Regular and well-promoted festivals significantly boost both international reputation and local economic impact. Keywords : Tourism, Samarkand, Festivals, Gastronomic Tourism, Destination Attractiveness